Ocorrência de Pasteuria nishizawae em áreas de soja e controle de Heterodera glycines em casa de vegetação - Vicente, Camilla Buiatti (2014)
Soybean (Glycine max (L.) Merrill) is a crop of great economic importance. Brazil is the second largest producer and exporter. One of the most serious disease problems of this culture is the cyst nematode Heterodera glycines (Ichinohe), considered as its most destructive parasite. The first occurrence of this disease in Brazil was reported in the 1991/1992 harvest. Nematode control is more difficult than that of other pathogens. Therefore, it becomes increasingly important to search for effective alternative control methods, reducing contamination risks to the environment and to the applicator. Thus, the bacterium Pasteuria spp. represents a promising, highly specific, agent for biological control of nematodes. The biological control of soybean cyst nematode by the bacterium Pasteuria nishizawae has proven an excellent choice and is being studied by many researchers. The objectives of this study were to determine the natural occurrence of Pasteuria nishizawae in Brazilian soils and compare infectivity in resistant soybean (P98Y12) and susceptible (experimental) cultivars, determining the efficiency of a product based on Pasteuria nishizawae in the control of Heterodera glycines. The tests were conducted in a greenhouse in Syngenta Research Unit in Uberlândia - MG, as well as in the Nematology Laboratory of the same Institution. Evaluations of field trials consisted of quantification of naturally occurring bacterium in soils, of the number of juveniles penetrated in each root system, of the number of cysts and of the number of eggs per cyst. Significant differences were observed in juvenile penetration rate between the resistant and susceptible soybean cultivars, which was greater in the susceptible one. Female indices were smaller in the susceptible cultivar after treatment with biological product. As Pasteuria nishizawae doses increased, juvenile penetration in roots and number of cysts formed decreased.